METODE BIBLIOTHERAPY PADA KISAH NABI YUSUF AS SEBAGAI MEDIA KONSELING RASIONAL EMOTIF - Neni Noviza (Wardah, 2013)
Bibliotherapy is an expressive therapy in which there is an individual relationship with the content or essence books , poems and other writings as a therapy . Bibliotherapy according to experts is one type of therapy that uses the activity of reading a piece of literature to address the problems faced by a person . Bibliotherapy assignments include reading to reading materials selected , planned , and directed as a procedure with the aim of therapeutic action . With bibliotherapy is believed to influence the attitudes , feelings , and behaviors of individuals as expected and may stimulate readers to think . Bibliotherapy easy to implement , inexpensive , and can be done anytime and involves the reader 's own self-sufficiency and full participation to internalize it . Provision of treatment need to be disseminated in the form of bibliotherapy as a method of meaningful action .Bibliotherapy in the story of Prophet Yusuf as very appropriate to be used as a medium of rational emotive counseling in changing pemikiraan irrational becomes rational thinking person that reflected the emotions and behavior in both in family life , school , and community environments . Surah Yusuf called by the Almighty as ahsanul qasasi ( most good stories ) , because it contains a lot of ' ibrah (lessons ) for people who have sense. Allah the Exalted says , " Surely the stories they were teaching there for people who have sense. The Koran is not a made-up story , but justify ( the books ) previously and explained everything , and a guidance and a mercy for people who believe . " ( Surah Yusuf , 12 : 111 )